PENGUATAN KARAKTER BERBASIS PELAJARAN BAHASA JAWA DI UPT SD NEGERI BABADAN 01 WLINGI BLITAR - Anwar, Choerul; Nusantara, Toto; Kusumaningrum, Shirly Rizki (Universitas Nahdlatul Ulama Blitar, 2024)
: The focus of the study in this article is to find out and analyze the positive characters in Javanese lessons and the role of teachers in strengthening character in Javanese lessons. The method used by researchers in this article is qualitative with a case study type. Data was obtained by interviews, observation and documentation. Meanwhile, data analysis is carried out in three simultaneous steps, namely data condensation, data display, and verification. The results of the research state that positive characters in learning Javanese include tolerance, compassion, mutual cooperation, respect, humanity, respect, gratitude, good manners, respect for friends and others, understanding self-placement, and honesty. These positive characters can be found in Javanese language lessons both implicitly and explicitly. Teachers have a major role in implementing positive character in Javanese language lessons. By example, the teacher not only conveys the material but also masters a lot of vocabulary in the Kromo language so that it can provide examples and role models.